Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found